Determinants of Farm Women's Participation in Shallot Farming and Processing Activities - Athasari, Hanita; Subejo, Subejo; Astuti, Umi Pudji (University of Jember, 2024)
Women farmers' participation is considered important for the development of shallot farming. Therefore, this study aims to analyze the factors that influence farm women's participation in shallot farming and processing activities in Selopamioro Village. Farm women's participation was calculated based on four stages of participation, namely participation in decision-making, implementation, benefit-taking, and evaluation. This study involved 50 farm women to be the sample in the study, which focused on Nawungan I and Nawungan II hamlets. This research was conducted using a quantitative approach, where there were 2 tests, namely the proportion test and multiple linear regression. The results of this study show that more than 50% of farm women have a high level of participation in shallot farming and processing activities. The highest level of participation is in the third stage, namely participation in benefit taking. Factors that significantly influence farm women's participation include motivation, cosmopolitan level, and intensity of attending extension services.